A case report of aorto-pulmonary window in an infant born to a diabetic mother. Issue 6 (December 2015) - Schena, Federico; Cappelleri, Alessia; Picciolli, Irene; Mayer, Alessandra; Francescato, Gaia; Galli, Maria Albina; Arcidiacono, Carmelo; Mosca, Fabio
Abstract: Several studies have described the association between pre-gestational maternal diabetes and cardiac disease in the newborn. Infants of diabetic mothers have an increased incidence of congenital heart disease, reported between 3% and 6% compared to 0.8% of the general population. A particularly high prevalence of conotruncal defects has been recently described among congenital heart diseases. This group of malformations affects ventricular outflows, aorta, and pulmonary artery and shares a common embryogenic origin. They include persistence of the truncus arteriosus, transposition of great arteries, tetralogy of Fallot, interruption of the aortic arch, and double outlet right ventricle. Aorto-pulmonary window, a rare congenital heart disease belonging to conotruncal malformations, has never been previously described in association with maternal diabetes. We describe the case of a male infant born to a mother suffering from a poorly controlled type 1 diabetes during pregnancy. In the early postnatal life the infant showed respiratory distress, tachycardia, and failure to thrive. He was found to be affected by aorto-pulmonary window that required corrective surgical intervention. <Learning objective: This case report warns us to consider this congenital abnormality as a possible finding in infants born to a diabetic mother. Furthermore, it shows how difficult the echocardiographic diagnosis of aorto-pulmonary windows can be.>